Carbon emission from biodiversity research conferences in Indonesia - Andes Hamuraby Rozak; Decky Indrawan Junaedi (Sustinere: Journal of Environment and Sustainability, 2022)
Participants in scientific conferences have been traveling to the cities of conference venues. These mobilizations left carbon footprints due to carbon dioxide (CO2) emissions generated from the scientists' transportation to their conference venue. This study looks at the carbon footprint of scientists who attended scientific biodiversity conferences in Indonesia from 2015 to 2019. We have identified that 30 scientific biodiversity conferences were conducted in 17 cities on five different islands during the corresponding period. The conferences have published 3092 scientific articles written by 9617 authors from various disciplines. The estimated carbon emission due to those scientists' transportation was 622 tons CO2-eq. This emission figure is almost equivalent to the emission produced by a person circling the earth 91 times using a passenger aircraft. A new paradigm of virtual conference should be considered to minimize the carbon footprint resulted from the scientists' transportation to and from the conference venue. Thus, the CO2-eq emissions released by scientists' transport can be reduced significantly. These emission reductions may mitigate and minimize the magnitude and impact of climate change to some extent.